IMPLEMENTASI KEBIJAKAN ENERGI LUAR NEGERI RUSIA DI HUNGARIA TAHUN 2021 – 2022 - Elsa Mulyani; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research is motivated by the existence of Russia which is present as a major producer in regional and global energy markets and is supported by large natural gas reserves so that it is able to maximize this potential as a tool/instrument in achieving its interests. Through the Foreign Energy Policy, Russia is trying to achieve a stable position in the energy market, especially in Hungary because of the strategic political-economic relations between the two countries. The purpose of this study is to analyze the implementation of Russia's Foreign Energy Policy in Hungary with the note that the country is part of the European Union and NATO which tends to be in opposition to Russia. This research use a qualitative method with Document Analysis data collection techniques which originate from writing in the form of books, journals, official documents, articles, websites and uses the theory of policy implementation. The result of the research show that the implementation of the Russian Foreign Energy Policy in Hungary is carried out through pragmatic cooperation so that the provisions and implementation are dynamic in accordance with the market conditions of the two working together. The theory of policy implementation also explains the implementation process by determining implementing actors, target actors, implementation procedures and the impact of the Foreign Energy Policy for the two countries involved. Keywords: Foreign Energy Policy, implementation, energy market, political economy